1982
DOI: 10.1038/299830a0
|View full text |Cite
|
Sign up to set email alerts
|

Denervation of newborn rat muscles does not block the appearance of adult fast myosin heavy chain

Abstract: Several observations, both in vivo and in vitro, have indicated that the development and maturation of mammalian skeletal muscle fibres is influenced by nerve-muscle interactions. Morphological maturation of newly regenerated adult mouse muscle fibers in an organotypic nerve-muscle culture system depends on the presence of spinal cord neurones. Sciatic nerve transection in newborn rats has been shown to modify the development of the histochemical and contractile properties of the denervated muscles. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(74 citation statements)
references
References 21 publications
4
69
1
Order By: Relevance
“…In accordance with these data, denervated slowtype soleus expressed exclusively the fast MHCIIX and IIB mRNAs in the regeneration process (Esser et al 1993;Jerkovic et al 1997). Other reports also suggest that IIB fibers develop in the absence of neural stimulation (Butler-Browne et al 1982;Schiaffino and Reggiani 1996;Fink et al 2003). Thus, the relatively small MHCIIB-expressing fibers, often located in the connective tissue-rich areas in our experiments, certainly represent denervated fibers that could not accomplish MHC transitions and growth.…”
Section: Discussionsupporting
confidence: 69%
“…In accordance with these data, denervated slowtype soleus expressed exclusively the fast MHCIIX and IIB mRNAs in the regeneration process (Esser et al 1993;Jerkovic et al 1997). Other reports also suggest that IIB fibers develop in the absence of neural stimulation (Butler-Browne et al 1982;Schiaffino and Reggiani 1996;Fink et al 2003). Thus, the relatively small MHCIIB-expressing fibers, often located in the connective tissue-rich areas in our experiments, certainly represent denervated fibers that could not accomplish MHC transitions and growth.…”
Section: Discussionsupporting
confidence: 69%
“…This suggests a potential role for innervation in regulation of MHC isoform protein expression. However, previous studies have suggested that innervation is not a requirement for the ultimate expression of adult fast MHC protein isoforms (6,8,27,32). Furthermore, during postnatal development of the rat Dia m , removal of innervation with unilateral denervation only delayed expression of fast MHC protein isoforms and prolonged expression of the MHC Neo protein isoform (39).…”
Section: Discussionmentioning
confidence: 99%
“…Histochemical ATPase staining was performed as described [23] with preincubation at pH 4.3 carried out at room temperature for 40 min. Characterization of the neonatal myosin antibody and methods for antigen and antibody purification, solid phase enzyme immunoassay, immunoblotting and indirect immunofluorescence have already been described [15,24,25].…”
Section: Methodsmentioning
confidence: 99%